Schmidt Hammer studies in the maritime Antarctic: Application to dating Holocene deglaciation and estimating the effects of macrolichens on rock weathering - GUGLIELMIN, MAURO; CANNONE, NICOLETTA; Worland M.R.; Convey P. (Geomorphology, 2012)
In order to contribute to the reconstruction of the deglaciation history of the Marguerite Bay area (similar to 68 degrees S, Maritime Antarctic) and to estimate the rock weathering rate in this Antarctic sector, 28 sites (7 on Rothera Point and 21 on Anchorage Island) were characterised using Schmidt Hammer values. The weathering effect of two of the most widespread species of macrolichens in this area (Usnea sphacelata and Umbilicaria decussata) was tested at 5 different sites on Rothera Point. Schmidt Hammer data, in conjunction with recent C-14 age, suggest a deglaciation age for the Marguerite Bay area of around 12 ka, and an average uplift rate of 5.4 mm year(-1) on Anchorage Island for the period between 3.3 and 5.2 ka. The weathering rates are extremely slow (e.g. three times slower than reported in Norway). Our data confirm that lichens exert a strong impact on weathering, decreasing the Schmidt Hammer R-values on lichenised surfaces by a factor of 3-4 compared to bare rock surfaces. The effect of lichens on weathering is mainly due to edaphic conditions and the type of the lichen involved rather the period of exposure.